Sharia Governance, Service Quality, and Muzakki Loyalty: Evidence from Amil Zakat Institutions in Indonesia - Nugraha, Fajar Putra; Herianingrum, Sri (Universitas Airlangga, 2025)
This study aims to determine the influence of Sharia governance and service quality on the level of loyalty of muzakki at Amil Zakat Institutions through a quantitative approach. The population of this study consists of muzakki who pay their zakat through Amil Zakat Institutions. Data collection was carried out by distributing questionnaires to 156 respondents who had previously paid their zakat at an Amil Zakat Institution. The sampling method used was non-probability sampling with a convenience sampling technique. Data analysis was conducted using the Structural Equation Modeling (SEM) method with the Partial Least Squares (PLS) model. The results of this study show that transparency, accountability, justice, sharia compliance, and service quality have a positive and significant influence on the loyalty of muzakki at Amil Zakat Institutions. The findings reinforce Oliver's loyalty model that